Investigating the relationship between quorum sensing, motility, and the type 3 secretion system of Yersinia pseudotuberculosis - Goldstone, Robert J. (2012)
Over the course of the last two decades, research into the role of quorum sensing (QS) in regulating diverse bacterial behaviours has exploded, and around twelve years ago, a QS network was identified in the enteropathogenic bacterium Yersinia pseudotuberculosis, which was shown to control motility and cellular clumping. This thesis seeks to expand this regulatory relationship and explore the causes and consequences of the link between QS and motility, which affects pleiotropic processes including the type 3 secretion system (T3SS) and biofilm formation. Indeed, the clumping phenotype first explored by Atkinson et al. (1999), is linked to QS-dependent regulation of the T3SS, since the deletion of several QS genes results in liquid culture biofilm (LCB) formation. This is concomitant with T3S protein secretion into culture supernatant, which occurs under normally non-inducing conditions, while deleting the T3SS structural component yscJ prevents secretion and LCB formation. De-repression of the T3SS and the development of LCBs also occurs following mutation of the flagella regulators flhDC and fliA, revealing that QS and the flagella system co-regulate LCBs. However, interestingly it was found that LCB formation and secretion also occurs following mutation of the flagella structural gene flhA. The ΔflhA mutant represents a flagella-minus strain, in which the underlying regulatory circuit mediated by FlhDC and FliA is intact, suggesting that an element of the flagella structure that depends on FlhA activity acts as a check-point governing expression of the T3SS.